Alcohol consumption during pregnancy and perinatal results: a cohort study - Sbrana, Mariana; Grandi, Carlos; Brazan, Murilo; Junquera, Natacha; Nascimento, Marina Stevaux; Barbieri, Marco Antonio; Bettiol, Heloisa; Cardoso, Viviane Cunha (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Alcohol consumption during pregnancy is a significant social problem that may be associated with adverse perinatal outcomes. The aim of this study was to describe alcohol consumption during pregnancy and to study its association with low birth weight, newborns small for gestational age and preterm birth. DESIGN AND SETTING: Nested cohort study, in the city of Ribeirão Preto, São Paulo, Brazil. METHODS: 1,370 women and their newborns were evaluated. A standardized questionnaire on health and lifestyle habits was applied to the mothers. Anthropometry was performed on the newborns. Alcohol consumption was defined as low, moderate or high, as defined by the World Health Organization. Adjusted logistic regression analysis was used. RESULTS: 23% of the women consumed alcohol during pregnancy. Consumption mainly occurred in the first trimester (14.8%) and decreased as the pregnancy progressed. The median alcohol intake was 3.89 g (interquartile range, IQR = 8 g) per day. In the unadjusted analysis, alcohol consumption increased the risk of low birth weight almost twofold (odds ratio, OR 1.91; 95% confidence interval, CI: 1.25-2.92). The risk was lower in the adjusted analysis (OR 1.62; 95% CI: 1.03-2.54). Alcohol consumption did not show associations with small for gestational age or preterm birth. There was greater risk of low birth weight and newborns small for gestational age and preterm birth among mothers who were both smokers and drinkers. CONCLUSIONS: The alcohol consumption rate during pregnancy was 23% and was independently associated with low birth weight, but there was no risk of newborns small for gestational age or preterm birth